2018
DOI: 10.1111/nyas.13614
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to relate accommodative visual dysfunctions to neck pain?

Abstract: The aim of this study was to establish whether there is a relationship between conditions of accommodative visual dysfunctions and cervical complaints. Fifty-two participants were included. Variables were accommodative amplitude, positive and negative relative accommodation (NRA), accommodative response, and accommodative facility. Subjects were classified as accommodative insufficiency, accommodative excess, or normal. Neck complaints were measured with the Neck Disability Index, the Visual Analogue Scale, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 68 publications
(190 reference statements)
1
17
0
Order By: Relevance
“…One study was a case series study . Three studies were observational cohort and cross‐sectional studies . Two studies were controlled interventional studies .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study was a case series study . Three studies were observational cohort and cross‐sectional studies . Two studies were controlled interventional studies .…”
Section: Resultsmentioning
confidence: 99%
“…Some other authors determined an accommodative function state through a test that demonstrated high repeatability and established a relationship between accommodative dysfunctions and neck complaints.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A decreased range of cervical motion and neck pain have been reported as co-occurring symptoms in accommodative dysfunctions. 37 , 38 The common sympathetic innervation link that is shared with the accommodation system is proposed as one possible reason for this. Nonetheless, neck pain can also be secondary in AI owing to abnormal neck and head retractions during reading resulting from the visual fatigue and blur.…”
Section: Methodsmentioning
confidence: 99%